Pertanggungjawaban Kepada Investor Reksadana Yang Mengalami Kerugian Akibat Wanprestasi Yang Dilakukan Manajer Investasi (Jurnal Begawan Hukum (JBH), 2024)
Parties or companies that manage their customers' managed funds into various investment instruments are known as investment managers in mutual funds. Mutual funds are highly recommended for novice investors because of their low capital and risk compared to other types of investment. In managing mutual funds, the investment manager is responsible for the securities portfolio and the collective investment portfolio. The portfolio is intended to minimize the risks that occur when managing investments, with the existence of a portfolio it is expected that the returns expected by investors can be achieved optimally in managing mutual funds. In managing mutual funds, there are always mistakes in anticipating the return expected by investors. Default is one example of an error that occurs. There are two causes of default: debtor (customer) and force majeure (overmacht or force majeure).